Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Solve the system of equations: $$\begin{cases}\dfrac{x^2+xy+y^2}{x^2+y^2+1}=\dfrac{1}{xy} \\\left(\sqrt{3}+xy\right)^{\log_2x}+\dfrac{x}{\left(\sqrt{3}-xy\right)^{\log_2y}}= 1+\dfrac{x}{y}\end{cases}$$

My try: $\dfrac{x^2+xy+y^2}{x^2+y^2+1}=\dfrac{1}{xy}\\\Leftrightarrow xy\left(x^2+y^2\right)+\left(xy\right)^2= x^2+y^2+1\\\Leftrightarrow\left(xy-1\right)\left(x^2+y^2+xy+1\right)=0\\\Leftrightarrow xy=1\,\,\,\mbox{(because:}\,\, x^2+y^2+xy+1>0)$

And here I'm stuck!

share|cite|improve this question
if i answered your question then please mark it so! – calmyoursenses Nov 10 '13 at 6:33

1 Answer 1

up vote 1 down vote accepted

Subsitute $xy=1 , y=1/x,and \, log y=-logx$ :-

$log(3^{1/2}+1)^{logx}+ x*log(3^{1/2}-1)^{logx}=1+x^2$

then take Log at both sides of your equation then your 2nd equation becomes

$logx*log(3^{1/2}+1)+logx+ logx*log(3^{1/2}-1)=2logx$

$log(3^{1/2}+1)+ log(3^{1/2}-1)=1$


which is always true!

share|cite|improve this answer
of course i have leap frogged some steps. – calmyoursenses Nov 9 '13 at 17:45

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.